Analisis Penerapan Penilaian Sikap Dalam Kurikulum 2013 Pada SMA Negeri 1 Tajur Halang - Salma Zakiyah; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
Curriculum 2013 has an assessment of learning in schools that includes the 3 domain of learning, which is attitude, knowledge, and skill assessment. This study aims to analyze applications in the attitude assessments found in the 2013 curriculum on SMA Negeri 1 Tajur Halang. As for the method used is a descriptive method with a qualitative approach. Data drawn using interview and documentary techniques from sources working at SMA Negeri 1 Tajur Halang. Studies show that, SMA Negeri 1 Tajur Halang already undergoes good and consistent with the 2013 curriculum. Implementation of an attitude assessment is done with four stages, creating a assessment plan, establishing the technique to be used, executing an attitude assessment consistently and thoroughly, and analyzing the results of the assessment. In addition, assessments of attitudes are done with four techniques: observation, self-assessment, peer assessment, and journal assessment.